Pelayanan Pastoral Terhadap Pemindahan Jenazah Ke Patane dalam Konteks Budaya Toraja dan Iman Kristen: Studi Kualitatif Pelayanan Pemakaman di GBT Sei Menggaris Kalimantan Utara - Firmansah, Endik; Adi, Didit Yuliantono (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
This study explores the service of transferring bodies from the grave to Patane in the context of Torajan culture and Christian teachings. The main focus of this study is on the pastoral decision not to repeat the funeral ritual during the transfer of the body, but to hold a thanksgiving prayer for the completion of the construction of Patane, with the main aim of providing comfort to the bereaved family. This approach is analyzed through a study of Torajan cultural values ​​that respect the funeral process as an important part of the human life journey, the history of funeral traditions in Christianity, and biblical interpretations of funerals and transfers of bodies, including the practice of Jesus' burial and the transfer of Joseph's body. This study also examines theological views on the meaning of death, burial, and respect for the body in the context of local culture. By understanding these dynamics, this study seeks to show how pastoral care can adapt to local culture without ignoring the values ​​of Christian faith. The results of this study are expected to contribute to church services, especially in accompanying grieving families in the midst of a cultural context rich in tradition such as the Torajan community.